1996
DOI: 10.1111/j.1469-8137.1996.tb01897.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a mycophagous Collembola on the symbioses betweenTrifolium subterraneumand three arbuscular mycorrhizal fungi

Abstract: SUMM.4RYWe examined the effect of the mycophagous Collembola Folsomia Candida Willem on the symbioses between Trifolium subterraneum L. and three arbuscular mycorrhizal (AM) fungi. Mycorrhizal and non-mycorrhizal plants were grown in pots with a central mesh bag -ivhich constituted a root-free soil compartment (RFSC) where the soil was labelled w-ith ^^P. This allow^ed us to study hypha] P transport as affected by the presence of CoUemhola in the soil with roots. The hyphal P transport w-as monitored by measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 28 publications
1
15
0
1
Order By: Relevance
“…Reduced root biomass in presence of collembolans has been observed in a number of studies (Larsen and Jakobsen 1996, Bardgett and Chan 1999, Scheu et al 1999, Kreuzer et al 2004) and has been ascribed to a collembolan-mediated increase in plant nutrient uptake (Lussenhop and BassiriRad 2005). Compared to roots earthworms disproportionately increased shoot biomass, resulting in an increased shoot-to-root ratio.…”
Section: Earthworms and Collembolansmentioning
confidence: 95%
“…Reduced root biomass in presence of collembolans has been observed in a number of studies (Larsen and Jakobsen 1996, Bardgett and Chan 1999, Scheu et al 1999, Kreuzer et al 2004) and has been ascribed to a collembolan-mediated increase in plant nutrient uptake (Lussenhop and BassiriRad 2005). Compared to roots earthworms disproportionately increased shoot biomass, resulting in an increased shoot-to-root ratio.…”
Section: Earthworms and Collembolansmentioning
confidence: 95%
“…However, given that in grasses it has been shown that the AM symbiosis can afford increased resistance to fungal pathogens (Newsham et al, 1995) the observed reduction in AM colonization might carry a cost which could not be detected in the current study. Indeed, Larsen & Jakobsen (1996) comment that whilst they found no effect of Collembola feeding in AM functioning, other studies had observed such a response and that impacts on the host might therefore, be contextually dependent. Further research, involving field trials would be desirable in order to clarify this issue.…”
Section: mentioning
confidence: 99%
“…However, fungal feeding microarthropods also detrimentally affect the hyphal network by severing hyphal branches at their bases even when offered a greater range of fungi as food sources [75]. The infection rate by arbuscular mycorrhiza and therefore plant growth was found to decrease with increasing collembolan density in pot experiments [44,58,81,85,88,129]. Microarthropod densities in laboratory experiments are often unnaturally high and moderate arthropod grazing which may be closer to what occurs in the field, has been shown to stimulate mycorrhizal growth [40,44,85,90].…”
Section: Mesofauna-fungi Interactionsmentioning
confidence: 99%